2021
DOI: 10.1111/pai.13454
|View full text |Cite
|
Sign up to set email alerts
|

New concepts in pediatric rhinitis

Abstract: Rhinitis-and especially allergic rhinitis (AR)-remains the most frequent hypersensitivity condition, affecting up to a quarter of the population and impacting the quality of life of individual patients and the health economy. Data, especially with respect to underlying pathophysiologic mechanisms, mainly derive from studies on adults and are subsequently extrapolated to the pediatric population. Therapeutic algorithms for children with rhinitis are long based on the same principles as in adults. We explore and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 131 publications
(136 reference statements)
0
18
0
5
Order By: Relevance
“…Besides AR, children and adolescents can suffer from non‐allergic rhinitis (NAR) 2 . The differentiation between these phenotypes has classically been based on the results of skin prick test (SPT) and serum allergen–specific IgE (sIgE) (collectively called atopy tests) 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides AR, children and adolescents can suffer from non‐allergic rhinitis (NAR) 2 . The differentiation between these phenotypes has classically been based on the results of skin prick test (SPT) and serum allergen–specific IgE (sIgE) (collectively called atopy tests) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the atopy‐based division of chronic rhinitis is being progressively replaced by an allergy‐based classification grounded on the pattern of nasal allergen–specific reactivity. In this regard, AR patients are defined as those showing positive NAC, SPT, and/or serum sIgE results 2,3 . Conversely, the NAR phenotype comprises a heterogeneous group of diseases, who only share the negativity of the NAC 8 .…”
Section: Introductionmentioning
confidence: 99%
“…AR is a Th2-type inflammatory disease of the upper airways. 24,25 It is diagnosed on the basis of the pathogenesis, i.e, IgE antibody to an aeroallergen, IgE-mediated mast cell activation leading to mucosal symptoms such as rhinorrhea, nose itching, sneezing, blocked nose, and eosinophilic inflammation of the nasal mucosa leading to nasal hyper-reactivity. Positive findings for the "triad" of AR criteria, i.e., 1) "allergic" nasal symptoms, 2) aeroallergen sensitization and 3) nasal eosinophilia, can establish the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Multimorbidity is a characteristic feature of allergies in children. 25 The MeDALL (Mechanisms of the development of ALLergy) study, involving 12 cohort studies, reported that coexistence of asthma, rhinitis and eczema in the same child was more prevalent than would be expected by chance. 29 An important aspect of multimorbidity is development of asthma, because it places the largest burden on children.…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications highlighted that house dust mite (HDM) was the most common allergen in perennial AR in southern regions of China (4,5). As a common disease, AR is also prevalent in children and affects 10% to 30% of this population in the United States and other developed countries (6,7). Accordingly, AR was closely associated with asthma and allergic conjunctivitis and, carried a heavy disease burden for children including attention and memory deficits, fatigue, sleep-deprived and even depression (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%